Iranian nurses' attitudes towards the necessity and barriers to developing nurse prescribing roles - Azam Naderi; Maryam Janatolmakan; Rostam Jalali; Bahare Andayeshgar; Alireza Khatony (BMC, 2021)
Abstract Background Prescribing medication by nurses as an approach to rational drug prescription has been proposed in many countries. Nursing prescribing is an effective measure in the management of critically ill patients admitted to intensive care units (ICU). This study investigated the attitude of ICU nurses towards the necessity and the barriers to developing nursing prescribing. Materials and methods In this cross-sectional study, 136 ICU nurses were included by stratified random sampling. The data collection tool was the researcher-made questionnaire. Cronbach's alpha method was used to evaluate the reliability of the instrument. The validity of the instrument was also verified by the content validity method. To collect the data, the researcher referred to the nurses' workplace and provided them with a questionnaire and collected it after completion.The collected data were analyzed by IBM SPSS 16 using descriptive and inferential statistics. Results It was revealed that 58.8 % of nurses were familiar with the term 'nursing prescribing'; a majority (92.1 %) of whom considered it vital to develop this role in the ICU. Moreover, 86 % (n = 98) of the nurses assumed that it is possible to implement this role in ICU. The most potential barriers to its implementation were lack of legitimacy, disapproval of physicians, and the reluctance of nursing managers. Conclusions Most nurses maintained a positive attitude towards nursing prescribing; hence, its legitimacy seems vital in ICUs. For the development of the 'nurse prescribing' role, the Nursing System Organization may be helpful.